Operations management production of goods and services - McClain, John O. (The Prentice-Hall, 1985)
Geared towards problem solving and problem recognition, this text details various aspects of operations management. It includes a discussion of multi-level distribution systems and production scheduling in large organizations, as well as productivity measurement and improvement.